EP 82. Lateralization of auditory-motor and somatosensory-motor loops during bimanual auditory-paced finger tapping. Issue 9 (September 2016) - Gompf, F.; Pflug, A.; Kell, C.
Abstract : Introduction: During asymmetric bimanual movements the right hand usually performs the faster movement compared to the left hand. This left hemisphere preference for processing of higher relative frequencies has been postulated in the sensory domain. The left hemisphere is thought to excel in analyzing higher relative stimulus frequencies while the right hemisphere is more engaged in processing lower relative frequencies (Ivry and Robertson, 1998 ). The observed preference of right hand tapping the faster rhythm in 1:n bimanual tapping could potentially mirror this left hemisphere dominance for processing higher relative frequencies in the motor domain. The bimanual coordination of preferred movements has been related with activation of the left more than right supplementary motor area (SMA) (Jäncke et al., 2000 ). The intra- and interhemispheric interactions during asymmetric finger tapping and their relationship to hemispheric specialization for relative frequencies are not understood. We thus investigated the lateralization of neural networks engaged in bimanual coordination and explored the effect of tapping frequencies. Methods: In an EEG-fMRI experiment, 32 right-handed subjects performed an auditory-paced finger tapping task during which the tapping frequency (low/high) and the executing hand (unimanual left/right and bimanual) were modulated. Auditory clicks were presented at 2.5 Hz. The ratio of low versus high tapping frequency was 1:4 clicks. Here, we report the fMRI results first. Conditions of interest were randomized, blocked, and contrasted against silent baseline. EPI images were standard pre-processed and analyzed using a general linear model in SPM 12. Results are presented at p . Results: Right auditory association cortex activated more strongly in bimanual slow compared to fast tapping. The non-preferred asymmetric bimanual condition (left hand fast / right slow) activated the right SMA and right secondary somatosensory cortex (S2) more strongly than the preferred symmetric condition. This effect was independent of the left hand tapping frequency, as it was observed when tapping frequency was controlled for. Conclusion: These findings indicate that the right auditory association cortex specifically engages for slow tapping when 1:4 tapping requires auditory processing of larger time windows in the absence of timing information from the motor system. Our results suggest processing during the non-preferred asymmetric bimanual tapping engages an additional right-hemispheric somatosensorimotor feedback loop (involving S2 and SMA).The left hemisphere does not require this loop to the same extent when performing the identical movement. We speculate that this is a consequence of a left hemispheric dominance in auditory-motor integration (4). We conclude that only the non-dominant right hemisphere uses more somatosensory feedback when it is forced to perform precisely timed finger tapping at higher relative frequencies. This could be taken as indirect evidence for a left hemispheric specialization for auditory-motor integration at higher relative frequencies.